2021
DOI: 10.3389/fpsyg.2021.635534
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization and Coordination of Art Performances in Highly Competitive Contexts: Battle Scenes of Expert Breakdancers

Abstract: In the performing arts, such as music and dance performances, people actively interact with each other and show their exciting performances. Some studies have proposed that this interaction is a social origin of the performing arts. Some have further investigated this phenomenon based on the synchronization and coordination theory. Though the majority of these studies have focused on the collaborative context, several genres of the performing arts, such as jazz sessions and breakdance battles, have a competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The results of this study underscore the importance of multivariate methods for the study of human motoric coupling, which is multidimensional in nature. At least in dance research, both individual rhythmic entrainment and social coupling studies have often been based on the analysis of a single marker (Brown & Meulenbroek, 2016; Ellamil, Berson, Wong, Buckley, & Margulies, 2016; Shimizu & Okada, 2021; Solberg & Jensenius, 2019; von Zimmermann et al., 2018) or a single‐body region (Sato, Nunome, & Ikegami, 2014) per dancer. However, different types of multivariate approaches, including latent space (Hartmann et al., 2019) and time‐frequency analysis (Toiviainen & Hartmann, 2022) methods, have shown to outperform univariate ones such as correlations between vertical head velocities.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study underscore the importance of multivariate methods for the study of human motoric coupling, which is multidimensional in nature. At least in dance research, both individual rhythmic entrainment and social coupling studies have often been based on the analysis of a single marker (Brown & Meulenbroek, 2016; Ellamil, Berson, Wong, Buckley, & Margulies, 2016; Shimizu & Okada, 2021; Solberg & Jensenius, 2019; von Zimmermann et al., 2018) or a single‐body region (Sato, Nunome, & Ikegami, 2014) per dancer. However, different types of multivariate approaches, including latent space (Hartmann et al., 2019) and time‐frequency analysis (Toiviainen & Hartmann, 2022) methods, have shown to outperform univariate ones such as correlations between vertical head velocities.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study underscore the importance of multivariate methods for the study of human motoric coupling, which is multidimensional in nature. At least in dance research, both individual rhythmic entrainment and social coupling studies have often been based on the analysis of a single marker (Brown & Meulenbroek, 2016;Ellamil et al, 2016;von Zimmermann et al, 2018;Solberg & Jensenius, 2019;Shimizu & Okada, 2021) or a single body region (Sato et al, 2014) per dancer. However, different types of multivariate approaches, including latent space (Hartmann et al, 2019) and timefrequency analysis (Toiviainen & Hartmann, 2022) methods, have shown to outperform univariate ones such as correlations between vertical head velocities.…”
Section: Discussionmentioning
confidence: 99%
“…The humble origins of breaking [ 10 ] could perhaps explain this paucity of scientific literature. All that is available are studies on the improvement of physical abilities [ 11 ], the epidemiology of injuries [ 12 ], the acquisition of motor skills in dancers [ 13 ], cardiorespiratory profiles in b-boys [ 14 ] and sociological studies [ 15 ]. Despite scientific efforts made in this discipline and even with the pilot study on time-motion in breaking, for which only two world championships were analyzed [ 1 ], we still do not have longitudinal time-motion studies that allow us to analyze the evolution suffered in the sport and establish the most appropriate training loads for athletes.…”
Section: Introductionmentioning
confidence: 99%